Flux modeling for monolignol biosynthesis. (April 2019) - Wang, Jack P; Matthews, Megan L; Naik, Punith P; Williams, Cranos M; Ducoste, Joel J; Sederoff, Ronald R; Chiang, Vincent L
Graphical abstract: Highlights: Lignin biosynthesis is sufficiently complex that pathway behavior is not intuitive. Lignin flux models have been developed for poplar, alfalfa, and switchgrass. Constraint-based models predict pathway metabolic regulation including inhibition. Kinetic-based models accurately predict pathway flux dynamics and wood phenotypes. Modeling lignin biosynthesis guides engineering of cell-wall properties/utilization. Abstract : The pathway of monolignol biosynthesis involves many components interacting in a metabolic grid to regulate the supply and ratios of monolignols for lignification. The complexity of the pathway challenges any intuitive prediction of the output without mathematical modeling. Several models have been presented to quantify the metabolic flux for monolignol biosynthesis and the regulation of lignin content, composition, and structure in plant cell walls. Constraint-based models using data from transgenic plants were formulated to describe steady-state flux distribution in the pathway. Kinetic-based models using enzyme reaction and inhibition constants were developed to predict flux dynamics for monolignol biosynthesis in wood-forming cells. This review summarizes the recent progress in flux modeling and its application to lignin engineering for improved plant development and utilization.